Análise de necessidades do uso da língua inglesa na execução de tarefas em uma empresa multinacional - Onodera, Jorge (2010)
This research study took place in a Business Unit, a division of an American multinational company in de area of power systems located in the city of Guarulhos. This study aimed to carry out a Needs Analysis in ten departments of the Business Unit and to identify the working tasks performed by the employees in the target situation and the tasks that offer difficulties executing the job. The theoretical approach underpinning this study is based on the ESP approach to Language Teaching. For Teaching English for Business Purposes (EBP) this study was based on Ellis & Johnson (1994), Dudley-Evans & St John (1998); for Needs Analysis it was based on Hutchinson & Waters (1987), Strevens (1988), Brindley (1989), Berwick (1989), Robinson (1991), Dudley-Evans and St John (1998) and Long (2005). Data were obtained in the ten departments by using questionnaires and interviews. This research is in the qualitative paradigm and the methodology used was case study, oriented by Yin (2005), Stake (1988), Chizotti (2006) and Johnson (1992). The community focus of this study was the employees of a Business Unit division of an American Multinational that use the English Language to perform tasks. The target situation needs and also the language learning needs were identified. The results of this study identified relevant information about the main genres used in the company. Employees of the multinational company use the English Language mainly to: read and write e-mail, answer phone calls, participate in conference calls, write and make presentations. Data demonstrated difficulties in performing tasks like answering the telephone, participating in conference call, reading and writing presentations and the skill that causes problems while performing the tasks are listening-speaking; i.e. oral interactional skills. The results of this research may be used to generate syllabuses that can be used to supply the company general needs and also each specific department needs